Deteksi Perubahan Sebaran Klorofil-A Di Perairan Utara Aceh Menggunakan Citra Aqua Modis - Mursyidin Mursyidin (JTEV (Jurnal Teknik Elektro dan Vokasional), 2019)
This study examines supporting data for fishing around the northern periphery of Aceh which is 05 ° 00'00 "-06 ° 00'00" LU and 95 ° 00'00 "-96 ° 00'00" BT. the data used is Aqua MODIS satellite imagery data with a level-3 Standard Mapped Image (SMI) Monthly with a spatial resolution of 4 km. the process is done image cutting, data extraction, interpolaso, and overlays. during the east season 2018 to the west season 2019 the distribution of chlorophyll-a in the northern waters of Aceh tends to increase